Avascular necrosis of the right femoral head in a systemic lupus erythematosus patient - Ida Ayu Ratih Wulansari Manuaba; Bambang Setiyohadi (Indonesian Journal of Rheumatology, 2009)
According to the 1993 Association Research Circulation Osseous, idiopathic avascular necrosis of the femoral head is defined as the presence of disease or other causes that result in ischemic osteonecrosis of the femoral head without the presence of trauma or sepsis. Based on the above defi nition, idiopathic avascular necrosis(AVN) includes those that are the result of steroid administration, systemic lupus erythematosus, alcoholic consumption, etc. The pathogenesis of AVN is still obscure; however, it is basically caused by vascular circulation disorder, cell death and decreased capability of bone repair.1,2 Systemic lupus erythematosus (SLE) is characterized by the presence of systemic immune dysregulation, autoantibody formation, immune complex in the circulation, and activation of the systemic complement. The pathology during recurrence of SLE, among others, is the presenceof vascular lesion in the form of infl ammation, thrombosis, endothelial injury in which the three of them are predispositions for atherosclerosis. The vascular lesion will cause microcirculation damage which is a risk factor for the occurrence of AVN in activation of SLE. Besides being caused by vascular lesion during activation of SLE, AVN is also triggered by fat deposition in SLE patients as a result of long term steroid therapy that causes abnormal blood fat level.1,2 Patients with SLE who have undergone pharmacologic treatment with systemic steroid either in oral or injection form will have 10 to 40 times the risk of having idiopathic AVN. High dose of systemic steroid treatment of more than 4000 mg of prednisone administered for more than three months or low dose of oral steroid administered for seven days can become a risk factor for AVN. The mechanism of AVN caused by steroid treatmentis associated with hypercoagulation, fi brinolysis disorder, and thrombosis of the bone vein.1,2,3 We report a case of AVN of the right femoral head in an SLE patient.